From micro to macro hysteresis: Long-run effects of monetary policy - Felipe Alves; Giovanni L. Violante (Bank of Canada, 2024)
We develop a Heterogeneous Agent New Keynesian model with a three-state frictional labour market that is consistent with the empirical evidence that (i) low-skilled workers are more exposed to the business cycle, (ii) displacement leads to long-lasting earnings losses, and (iii) unemployment is a stepping stone toward exit from the labor force. In this environment, a transient contractionary monetary policy shock induces a very persistent reduction in labour force participation and labour productivity, especially among workers at the bottom of the skill distribution. Despite the negative hysteresis on output, the model does not give rise to protracted deflation.
Keywords: E21; E24; E31; E32; E52; J24; J64; 330; Monetary Policy Transmission; Labour Markets